Curriculum Development as a Critical Tool in the Education and Rehabilitation of Persons with Special Needs. - Bodang, Juliana Rotkanggmwa; Ozegya, A. E.; Ezeanochie, C. B. (NIU Journal of Social Sciences, 2018)
The paper seeks to X-ray the visible absence of a specific and operative philosophy (not objectives or goals) of Nigerian education in order to appropriately articulate curriculum development for children with special needs within the context of egalitarian ideology. The paper attempts formulating a humanistic-pragmatist philosophy which could be used to serve as a conceptual and interpretative framework for the education and rehabilitation of persons with special needs in Nigeria. The paper also highlights the socio-cultural needs of Persons with special needs in as well sa identified, analyzed and articulated within an evolving nascent and experimental democratic political setting. In conclusion, the paper discusses the existing Eurocentric and elitist curriculum framework and synthesized / integrated with a re-discovered and reformulated Pastoral Care curriculum (SNEC) anchored on enabling life skills and Human Survival Categories. Such an empowerment curriculum, which in reality is a marriage of the official, the Hidden and the Pastoral Curricula, has the potential of accommodating the special needs {content and pedagogical of the handicapped children in and out of the regular schools.  Its built in flexibility and teacher prone approaches make it particularly applicable to urban and rural Nigerian communities because it breaks the traditional barriers between school and everyday knowledge. At the heart of the education and rehabilitation strategies, the overall concern of the Special Needs Empowerment Curriculum (SNEC) development for this project is aimed at arranging, modifying and strengthening the educative environments {formal, informal, non-formal} in which children with special needs grow and develop. In this way, the experiences which they encounter construct and re-interpret will at once satisfy their special needs as well as shape their learning in ways which fit the uncertain and changing future.